Interaction of law enforcement bodies of Ukraine in disclosure of offenses and crimes: international standards and foreign experience - Leheza, Yevhen; Liudvik, Valentyn; Filipp, Anastasiia (DIXI, 2023)
The purpose of the research is to study the interaction of law enforcement bodies during the investigation of criminal offenses in accordance with international standards. The main areas of cooperation between law enforcement bodies in different states during the investigation of criminal offenses are highlighted. Recently, taking into account the great public danger of criminal offenses, it is worth noting that they have long acquired a transnational nature, and it is worth focusing special attention on the issue of cooperation between the National Police of Ukraine and international organizations on investigation of this category of criminal offenses. The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, as well as methods of analysis and synthesis. Attention is drawn to the issue of cooperation between operational units of the National Police dealing in combating criminal offenses, and to the issue of foreign law enforcement bodies performing operational and investigative activities.